Treatment related toxicity in BRCA1-associated epithelial ovarian cancer – is DNA repairing impairment associated with more adverse events? - Badora-Rybicka, Agnieszka; Budryk, Magdalena; Nowara, Elżbieta; Starzyczny-Słota, Danuta (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: The presence of BRCA germline mutations in patients with ovarian cancer has been shown to have predictive and prognostic significance, including increased platinum-sensitivity. The aim of the study was to evaluate if patients with BRCA1-associated ovarian cancer have more treatment related adverse events and, if so, does it have impact on chemotherapy outcomes. Material and methods : We conducted a retrospective analysis of medical records of 172 patients with newly diagnosed epithelial ovarian cancer, treated in Maria Skłodowska-Curie Memorial Cancer Center and Institute of Oncology, Gliwice Branch between 2007 and 2013. Ninety-six of these patients have known BRCA mutation status – 21 patients were BRCA1(+) and 75 BRCA1(–). Analysed treatment related adverse events (AE’s) were: haematological toxicity, nausea/vomiting, neuropathy and mucositis. Results : Grade 3–4 haematological AE’s were significantly more common among BRCA1(+) patients (OR = 3.86; 95% CI: 1.14–13.23; p = 0.02). There was no association between BRCA1 mutation status and neuropathy (p = 0.73) or nausea/vomiting (p = 0.91). Occurrence of above mentioned AE’s has no significant association with PFS (p = 0.75, 0.64, 0.97 respectively) and OS (p = 0.64, 0.69, 0.73 respectively). Conclusions : Among patients with BRCA1-associated epithelial ovarian cancer we observed significantly more grade 3–4 haematological complications after chemotherapy. However, occurrence of AE’s did not correlate with better outcomes in this subgroup.